Tinjauan Yuridis Perlindungan Hukum terhadap Pengguna E-Wallet atas Kehilangan Dana Akibat Kebocoran Data dan Transaksi Tidak Sah dalam Perspektif Hukum Perdata - Muhammad Daffali Maulindo; Muhammad Agung Antomy (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The rapid growth of e-wallet usage as a non-cash payment instrument in Indonesia has significantly transformed digital financial transactions, while simultaneously increasing the risk of personal data breaches and unauthorized transactions that result in financial losses for users. Numerous large-scale data breach incidents and the rising number of consumer complaints indicate that digital security systems and legal protection mechanisms for e-wallet users remain inadequate. This situation raises legal concerns regarding the civil liability of e-wallet service providers in ensuring the security of user data and funds. A normative juridical approach is applied by examining statutory regulations, legal doctrines, and relevant literature related to consumer protection and personal data protection through library research. The analysis demonstrates that e-wallet providers may be held civilly liable when negligence in safeguarding systems and personal data leads to consumer losses, as regulated under the Civil Code, Consumer Protection Law, and Personal Data Protection Law. Furthermore, existing legal protection frameworks have not fully accommodated the complexity of digital financial risks, particularly in terms of regulatory enforcement and dispute resolution mechanisms. Strengthening technical regulations, supervisory roles of authorities, and accessible legal remedies is therefore essential. A more comprehensive legal protection model is required to enhance legal certainty and ensure fair protection for e-wallet users within Indonesia’s evolving digital financial ecosystem.